Influence of Enjoyment and Trust on the Use of Artificial Intelligence-based Voice Assistant in Vocational Students Using Technology Acceptance Model (TAM) - Octavia, Agnes Christa Belliem; Nugraha, Jaka (Journal of Office Administration : Education and Practice, 2024)
This study aims to analyze the effect of enjoyment and trust on using artificial intelligence-based voice assistants in vocational high school students using TAM. The subjects of this study were students of the Program of Office Management and Business Services (OMBS) at Buduran Vocational High School. A sample of 140 students was selected from a population of 219 using the Krejcie and Morgan formula, with a significance level of 0.05. The study used Variance-Based Structural Equation Modeling (VB-SEM) with the GSCA pro software. The results showed that enjoyment and trust significantly influence perceived usefulness, perceived ease of use, behavioral intention, and actual use. In addition, this research model successfully explains the variability of the dependent variable with a FIT value of 0.522 and AFIT of 0.515, indicating that the model has a good level of fit. The findings emphasize the importance of enjoyment and trust factors in the acceptance of new technologies in educational settings and provide insights for the further advancement and integration of artificial intelligence technologies in vocational education.